The complete chloroplast genome of an economic plant, Camellia sinensis cultivar Anhua, China. Issue 2 (3rd July 2018) - Dong, Meng; Liu, Shiquan; Xu, Zhenggang; Hu, Zhiyuan; Ku, Wenzhen; Wu, Liang
Abstract: In order to supply genetic information of Camellia sinensis cultivar Anhua, characterization of the complete chloroplast genome sequence was reported based on high-throughput sequencing data. The complete cp genome of C. sinensis cultivar Anhua is shorter than other C. sinensis cultivars with 157, 025 bp in length, comprising a large single copy (LSC) region of 86, 585 bp and a small single copy (SSC) region of 18, 276 bp, separated by two inverted repeat regions (IRs) of 26, 082 bp. The overall G + C content is 37.30%. The genome contained total of 135 genes, including 90 protein coding genes, 37 tRNA genes, and 8 rRNA genes. Phylogenetic analysis showed all the cultivars were clustered into a group except C. sinensis var. pubilimba.